ANALISIS PENGARUH SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS ) TERHADAP EFEKTIFITAS DAN EFISIENSI PELAYANAN PASIEN KLINIK ALTARA, KOTA MEDAN SUMATERA UTARA TAHUN 2023 - Br Surbakti, Desi Natalia (Jurnal Kajian Kesehatan Masyarakat, 2025)
Hospital Management Information System, hereinafter abbreviated as SIMRS, is a communication information technology system that processes and integrates the entire flow of hospital service processes in the form of a network of coordination, reporting and administrative procedures to obtain precise and accurate information, and is part of the Health Information System. The aims of the research is to analyse the effectiveness and efficiency of implementing SIMRS for patient services at the Altara clinic. The method of the research is to use descriptive analysis with the interview method. The population of the research is employees at Altara clinic with a sample size of 10 respondents consisting of 9 main respondents and 1 triangulation respondent (patient). The results of the research are the influence of SIMRS Human Resources on the effectiveness and efficiency of patient services at Altara clinic , that SIMRS human resources are not in accordance with SIIMRS educational background, but all informants must take part in training which is conducted once a month for one hour so that the implementation of SIMRS is effective and efficient in service patient . SIMRS facilities and infrastructure factors for the effectiveness and efficiency of patient services at the Altara Clinic are complete so that patient services are effective and efficient. SIMRS operational procedure standards for the effectiveness and efficiency of patient services at the Altara Clinic have been provided so that harvest services are effective and efficient The conclusion of the research is that efficiency, trust and customer support have a relationship with patient satisfaction